Protective Benefits of Tending Ants to a Critically Endangered Butterfly. Issue 6 (12th December 2022) - Hill, Geena M; Trager, Matthew D; Lucky, Andrea; Daniels, Jaret C
Abstract: Ants provide protection to various organisms via myrmecophilous relationships. Most notably, ants and several butterfly species are involved in mainly mutualistic interactions. Previous field studies have shown that butterfly larval survival is increased in the presence of tending ants, suggesting that ants are providing protection against insect predation or parasitism. Here, we conducted a series of timed observational trials under laboratory conditions to assess larval survival and ant protection from insect predators for a myrmecophilous lycaenid butterfly. We focused on a critically endangered butterfly, the Miami blue ( Cyclargus thomasi bethunebakeri) (Comstock and Huntington) (Lepidoptera: Lycaenidae), and its most common ant associate, the Florida carpenter ant ( Camponotus floridanus ) (Buckley) (Hymenoptera: Formicidae), to test this assumption of ant protection. We found that ants provide significant protection to Miami blue larvae, with later instar larvae receiving a higher level of protection due to differences in tending frequencies. These results will aid in informing conservation management and future organism reintroductions for this endangered butterfly.